Penentuan Sistem Pengelolaan Limbah Domestik Berkelanjutan di Wilayah Padat Penduduk Bantaran Sungai Ciliwung (Studi Kasus: Kelurahan Cililitan) - Paramita, Nadia; Ningrum, Sari Sekar (Universitas Diponegoro, 2020)
The Ciliwung River is one of the main rivers flowing in the DKI Jakarta area. Ciliwung has an area of 370.8 km2, with a length of 124.1 km. The Ciliwung River contributes greatly to the communities in three big cities, namely Bogor, Depok and Jakarta as a source of drinking water, a source of raw water and a source of water for irrigation. The condition of household wastewater is currently discharged directly or indirectly into river water bodies. gray water is immediately discharged into the water body without being treated. Blackwater is treated to inadequate septic tanks or discharged directly into water bodies. This condition certainly requires a fast and precise solution and handling. In terms of domestic wastewater management, both gray water and black water, at this time Cililitan village is not included in the area that is accessible to centralized wastewater piping or off-site systems and does not have land that can be used to make a communal system waste treatment so that most of the households still throw away directly into the river or using a septic tank without regular desludging. The purpose of this study is to identify the current waste management conditions in Cililitan Village and provide recommendations for the selection of a sustainable domestic waste management system that is acceptable to the community and safe for the environment.